PENGARUH PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA PESERTA DIDIK KELAS IV DI SEKOLAH DASAR NEGERI 20 MAKRAMPAI TAHUN PELAJARAN 2023-2024 - Andini Andini; Purniadi Putra; M. Sabiqul Huda (CV. ADIBA AISHA AMIRA, 2025)
The aim of this research is to determine and analyze the effect of project based learning on Indonesian language learning outcomes for class IV students at SDN 20 Makrampai for the 2023-2024 academic year. This research uses associative research with a quantitative approach. Data collection techniques use indirect communication techniques, namely using questionnaires and documentation techniques. The population in this study were all class IV students at SDN 20 Makrampai, totaling 27 students. The data analysis techniques used are descriptive statistical analysis and simple linear regression analysis. The research results show that; 1) Description of project based learning in Indonesian language lessons in class IV SDN 20 Makrampai based on the assessment results regarding project based learning is at a percentage of 75.29%. This indicates that project based learning is in the very good category; 2) Description of Indonesian language learning outcomes for students in class IV SDN 20 Makrampai based on daily test score data collected using documentation instruments, namely with a percentage of 41.11%. This indicates that the learning outcomes of class IV students at SDN 20 Makrampai are in the sufficient category; and 3) There is a significant influence between project based learning on Indonesian language learning outcomes for class IV students at SDN 20 Makrampai because the obtained value is sig = 0.037, meaning Sig < the significant criterion of 0.05. Thus, project based learning has an influence on Indonesian language learning outcomes for class IV students at SDN 20 Makrampai, namely 16.3% is the contribution of project based learning to Indonesian language learning outcomes, while the remaining 83.7% is influenced by other factors.